All We Need Is One Mic: A Call for Anti-racist Solidarity to Deconstruct Anti-Black Racism in Educational Leadership. Issue 1 (January 2021) - Genao, Soribel; Mercedes, Yaribel
In this article, we outline some of the vital measurements of racism and anti-blackness as a macro system in education. We contend that principal preparation programs have not explicitly prioritized anti-racist school leadership, while often resisting the possibilities of solidarity or one mic of knowledge to increase anti-racist dispositions. Considering the lexicon of whiteness as an assemblage, a racial discourse should be "supported by material practices and institutions, " that prepare educational leaders to examine anti-blackness curriculum that have been embedded as a standard method. We also posit that theoretical understanding of racism as global whiteness from a post-oppositional lens and decoloniality that will challenge the way racism is currently referenced in educational leadership scholarship. Moreover, current global and decolonial research gives way for a new vision of solidarity by humanizing scholarly resistance that cultivates a vision of community that regards differences of knowledge across groups and investigates racist policies and practices in educational leadership programs.